Evolution of Rehabilitation Counseling in Puerto Rico: Organizational and Legislative Efforts Evolución de la consejería en rehabilitación en Puerto Rico: Esfuerzos organizacionales y proyectos legislativos - Ángel A. Villafañe Santiago; José Lionel Velázquez Altagracia; Maribel Báez Lebrón (Universidad Nacional, Costa Rica, 2013)
The purpose of this paper is to explain a) the historical, organizational, and legislative efforts that have contributed to the development of the Rehabilitation Counseling profession, b) how these efforts have contributed to the development of the professional identity of the rehabilitation counselors and c) how these events have contributed to the development of programs and the provision of quality services to people with special needs in Puerto Rico. Through oral history and literature review, it is possible to recognize the importance of the establishment of the federal legislation that promoted the first program of services to people with special needs in the United States and Puerto Rico. Those legislative mandates have also promoted the development of the Rehabilitation Counseling profession in the 20th Century and the development of professional organizations that have been determinant for the professionalization. This paper illustrates how at the end of 1960, in Puerto Rico, the creation of the Rehabilitation Counselors Association (Asociación de Consejeros en Rehabilitación, ACER by its Spanish acronym) was critical for the transformation of the profession and for the creation of the Puerto Rico's Professional Society of Rehabilitation Counselors (Colegio Profesional de los Consejeros en Rehabilitación de Puerto Rico) at the beginning of the 21st Century. The study refers to the subsequent legislative efforts and the approval of new mandates as the amendment to the Puerto Rican Law of Mental Health made to include the Rehabilitation Counseling professionals among the professionals authorized to provide such services to people with mental health conditions in the country. After this theoretical historical review, it is concluded that although more marketing is required in terms of promoting the profession, this innovative profession has kept up-to-date over time, and that is a guarantee of the professional commitment to continue providing quality services to the persons with special needs. Recibido 4 de julio de 2013 • Corregido 8 de agosto de 2013 • Aceptado 15 de agosto de 2013 El propósito de este trabajo es presentar: a) los esfuerzos históricos, organizacionales y legislativos que han contribuido al desarrollo de la profesión de consejería en rehabilitación, b) cómo estos esfuerzos han aportado al desarrollo de la identidad profesional de los consejeros y consejeras en rehabilitación y c) cómo estos acontecimientos han contribuido a expandir el desarrollo de programas y la prestación de servicios de calidad para las personas con necesidades especiales en Puerto Rico. A través de la historia oral y la revisión de bibliografía se reconoce la importancia de la creación de la legislación federal que promovió el primer programa de servicios para personas con necesidades especiales en los Estados Unidos y Puerto Rico. Estos mandatos legislativos también han promovido el desarrollo de la profesión de consejería en rehabilitación en el siglo XX y el desarrollo de las organizaciones profesionales determinantes en el establecimiento de la profesión. Se ilustra cómo, a finales de 1960 en Puerto Rico, la creación de la Asociación de Consejeros en Rehabilitación fue fundamental para la transformación de la profesión y la creación del Colegio de los Profesionales de la Consejería en Rehabilitación de Puerto Rico, a principios del siglo XXI, así como la contribución de un grupo de personas relacionadas con esta. Se presentan, además, los esfuerzos legislativos posteriores y la aprobación de nuevos mandatos, incluyendo la modificación de la Ley de Salud Mental de Puerto Rico para incorporar a este profesional entre los profesionales que prestan servicios a las personas con problemas de salud mental en el país. Después de esta revisión teórica e histórica se concluye que, si bien la profesión aún necesita más mercadeo, es una profesión de vanguardia que se ha ido actualizando con el tiempo, lo que garantiza el compromiso profesional de seguir ofreciendo servicios de calidad a las personas con necesidades especiales.